Environmental Policy Design Characteristics and Technological Innovation Evidence from Patent Data - Johnstone, Nick (OECD Environment Working Papers, 2010)
This paper focuses on the issue of innovation and technology transfer in the areas of air pollution abatement, wastewater effluent treatment, solid waste management, and climate change mitigation. The paper describes the trends in innovative activity related to selected areas of pollution abatement and control technologies and their transfer internationally. It also discusses characteristics of environmental policy regimes that are amenable to encouraging innovation of environmental technologies, and provides empirical evidence on the role of various determinants (including general characteristics of countries' environmental policy regimes) in encouraging innovation